Retraction notice to “Effects of nanocapsules of poly-ε-caprolactone containing artemisinin on zebrafish early-life stages and adults” [Sci. Total Environ. 756 (2021) 143851] (Science of the Total Environment (2021) 756, (S0048969720373824), (10.1016/j.scitotenv.2020.143851)) - Charlie-Silva, Ives; Feitosa, Natália Martins; Fukushima, Hirla Costa Silva; Borra, Ricardo Carneiro; Foglio, Mary Ann; Xavier, Rogéria Maura Pazini; de Melo Hoyos, Daniela Chemin; de Oliveira Sousa, Ilza Maria [UNESP]; de Souza, Giovane Galdino; Bailone, Ricardo Lacava [UNESP]; de Andrade Belo, Marco Antonio [UNESP]; Correia, Sostenes Apolo Marcelino; et al. (Elsevier, 2024)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/locate/withdrawalpolicy). This article has been retracted at the request of the Editors-in-Chief. Post-publication, an investigation conducted on behalf of the journal by Elsevier's Research Integrity & Publishing Ethics team determined that one of the reviews for this manuscript was fictitious. The review was submitted under the name of a known scientist without their knowledge. The name and fictitious contact details of the reviewer were submitted by the Corresponding Author Guilherme Malafaia during the manuscript submission process. Although the paper was reviewed by additional reviewers chosen by the Editor, this breach compromised the editorial process. The Editors-in-Chief have lost confidence in the validity/integrity of the article and its findings and have determined that it should be retracted.